Effects of vaccines on clinical characteristics of convalescent adult patients infected with SARS-CoV-2 Omicron variant: A retrospective study - Wang, Jingyu; Dong, Henan; Zhao, Jie; Li, Tianning; Wang, Meng; Zhou, Chunlei; Mu, Hong (Frontiers in Microbiology, 2023)
Introduction: The protective effect of SARS-CoV-2 vaccines has become a global focus due to Omicron variant pandemic. The effects of various SARS-CoV-2 vaccines are diverse. However, studies on the effect of domestic vaccines on clinical characteristics in convalescent adult patients infected with the Omicron variant are lacking. Results: Adult patients infected with Omicron were enrolled, including 296 post-vaccination and 24 unvaccinated patients. The median age of the unvaccinated patients was higher than that of vaccinated patients. Binary logistic regression results suggested that Sinopharm and Sinovac vaccine was independent protective factors for relieving the severity of the Omicron variant infection. Three domestic vaccines significantly relieved inflammation and increased the SARS-CoV-2-specific antibody levels. Furthermore, Sinovac and CanSino vaccines had a better immune stimulation effect on increasing T lymphocytes levels in convalescent adult patients. In addition, three domestic vaccines have protective effects on preventing re-detectable positive (RP) result in convalescent adult patients. Conclusion: Although the three domestic vaccines cannot prevent the infection of the Omicron variant, it has a significant protective effect in adult patients. This study supports the policy of accelerating vaccination worldwide to combat the evolving and mutating SARS-CoV-2. Discussion: Omicron spreads faster and might escape antibodies more readily than previous variants, increasing the cases of reinfection and breakthrough infections in vaccinated people. Although vaccinated people are likely to have a much lower risk of severe disease from Omicron infection, many issues still need to be considered. Concerns about lower vaccine efficacy because of new variants might have changed our understanding of the COVID-19 endgame, disabusing the world of the notion that global vaccination is by itself adequate for controlling SARS-CoV-2 infection. The current data showed that vaccination with three domestic SARS-CoV-2 vaccines alleviates the disease severity of adult patients with COVID-19, reduces the inflammation level and the RP rate of convalescent adult patients, and enhances body’s defense against the virus in convalescent adult patients. Moreover, our study has highlighted that a combination prevention approach of vaccination and public health measures would be an eﬀective strategy.